"Salvation is from the Jews" (Jn 4:22): Aquinas, God, and the People of God - Ryan, Fainche (Studies in Christian-Jewish Relations, 2011)
Some believe that Pope Benedict XVI approaches interfaith relations more from the point of view of social, cultural and political cooperation than that of theological dialogue. This approach is deemed unsatisfactory by Daniel Madigan, an eminent speaker on interfaith matters. Madigan suggests that interreligious dialogue must be theological if it is to lead peoples of different faiths into deeper relationship with one another. This article will seek to illustrate the importance of this approach by a return to the thought of St Thomas Aquinas, considered by many to be the greatest medieval theologian. Serious dialogue with those of other faiths is not something new. Thomas engaged with thinkers from all traditions to whom he had access–Muslim, Jewish, pagan. His work shows not a fear of a diminution of his own faith through engagement with the “other” but an attempt to deepen it through the “others” experience of the Divine. Focusing specifically on his engagement with the Jewish people, Aquinas’ thoughts on the complex issues of predestination and election will be presented, with particular attention being given to his Commentary on Romans. The image of God with which he works shall be identified as key to his dialogue. It is the suggestion of this article that the image of God, of the Divine, with which one works is central to all engagement in interreligious dialogue, and herein may lie some of our problems, as well as rich potential for fruitful, truthful engagement.